Drought Tolerance of Some Eggplant Accessions (Solanum spp.) - Daniel Bobby Setyadi; Taryono Taryono; Rahmi Sri Sayekti (Agrotechnology Innovation (Agrinova), 2020)
Eggplant is one of the commodities that started to be favouritely consumed and had economics value. There were many factors that affect the growth and development process of plant. One of those many factors are the environment condition such as drought. This research aims to know the tolerance level of eggplant accessions to drought. Plants grew in two comparative conditions, normal and drought. Drought is given by using interval water application about every 7 days. Observations were carried out to growth and yield components and continue measuring the stress effect using drought sensitivity index. The results show that plants develop an adaptation mechanism to drought by reducing its growth and yield components to survive. The result of further test and drought sensitivity index show that half of accessions have good tolerance to drought. Acessons that had goof tolerance to drought were SLTE 2, SLTE 3, SLTE 5, SLTE 6, SLTE 8, SLTE 13, SLTE 15, SLTE 18, SLTE 42, and SLTE 44.acc